2009
DOI: 10.1007/s12603-009-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and clinical features in elderly patients with dementia: Differences according to dementia severity

Abstract: Important comorbidity conditions are common in elderly individuals with dementia. The patients with more severe dementia had poor functional status and higher frequency of neuroleptic use. Medical comorbidities should be taken into account in the management of patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 27 publications
4
41
0
1
Order By: Relevance
“…Disease stage and the care setting from which patients are recruited are likely to influence the prevalence of and identification of physical conditions across different study populations [4,[6][7][8]. For co-morbidity these results broadly agree with the findings of the only other large routine heath dataset published to date, which described administrative claims data and recorded higher comorbid conditions among people with dementia than their matched controls [9].…”
Section: Comparison With Related Worksupporting
confidence: 78%
See 1 more Smart Citation
“…Disease stage and the care setting from which patients are recruited are likely to influence the prevalence of and identification of physical conditions across different study populations [4,[6][7][8]. For co-morbidity these results broadly agree with the findings of the only other large routine heath dataset published to date, which described administrative claims data and recorded higher comorbid conditions among people with dementia than their matched controls [9].…”
Section: Comparison With Related Worksupporting
confidence: 78%
“…specialist or inpatient cohorts, specific dementia types) and the way in which comorbidity is measured [3][4][5][6][7][8][9]. The extent of multiple medication use (polypharmacy) in dementia has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…Higher medical comorbidity not only accelerates functional deterioration leading to the under-diagnosis and under-treatment of dementia and comorbid illnesses, but also has significant implications for poorer self-care, immobility, and polypharmacy [2224]. Our study showed the burden of comorbidities is significantly high in older adults with cognitive impairment.…”
Section: Discussionmentioning
confidence: 79%
“…Clinical data on this issue are scarce and somehow contradictory. In most studies, cancer seems to be a prevalent comorbidity for patients with AD, and for males in particular (Gambassi et al, 1999;Gasper et al, 2005), although specific proportions vary from 8% (Formiga et al, 2007(Formiga et al, , 2008 to almost 23% in patients with reported exposure to carcinogens (Yamada et al, 1999). Other studies find that the risk of developing cancer, in organs distant from the central nervous system, is lower among AD patients than in nondemented patients (Beard et al, 1996;Roe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%